The Glycerol-Induced Perfusion-Kinetics of the Cat Ovaries in the Follicular and Luteal Phases of the Cycle - Alexey A. Selifonov; Andrey S. Rykhlov; Valery V. Tuchin (Diagnostics, 2023)
The method of immersion optical clearing reduces light scattering in tissues, which improves the use of optical technologies in the practice of clinicians. In this work, we studied the optical and molecular diffusion properties of cat ovarian tissues in the follicular (F-ph) and luteal (L-ph) phases under the influence of glycerol using reflectance spectroscopy in a broad wavelength range from 200 to 800 nm. It was found that the reflectance and transmittance of the ovaries are significantly lower in the range from 200 to 600 nm than for longer wavelengths from 600 to 800 nm, and the efficiency of optical clearing is much lower for the ovaries in the luteal phase compared to the follicular phase. For shorter wavelengths, the following tissue transparency windows were observed: centered at 350 nm and wide (46 ± 5) nm, centered at 500 nm and wide (25 ± 7) nm for the F-ph state and with a center of 500 nm and a width of (21 ± 6) nm for the L-ph state. Using the free diffusion model, Fick’s law of molecular diffusion and the Bouguer–Beer–Lambert radiation attenuation law, the glycerol/tissue water diffusion coefficient was estimated as D = (1.9 ± 0.2)10−6 cm2/s for ovaries at F-ph state and D = (2.4 ± 0.2)10−6 cm2/s—in L-ph state, and the time of complete dehydration of ovarian samples, 0.8 mm thick, as 22.3 min in F-ph state and 17.7 min in L-ph state. The ability to determine the phase in which the ovaries are stated, follicular or luteal, is also important in cryopreservation, new reproductive technologies and ovarian implantation.